The next American revolution : sustainable activism for the twenty-first century - Boggs, Grace Lee (University of California Press, 2012)
A world dominated by America and driven by cheap oil, easy credit, and conspicuous consumption is unraveling before our eyes. In this powerful, deeply humanistic book, Grace Lee Boggs, a legendary figure in the struggle for justice in America, shrewdly assesses the current crisis--political, economical, and environmental--and shows how to create the radical social change we need to confront new realities. A vibrant, inspirational force, Boggs has participated in all of the twentieth century's major social movements--for civil rights, women's rights, workers' rights, and more. She draws from seven.